PENGARUH FINANCIAL STABILITY, INEFFECTIVE MONITORING, PERSONAL FINANCIAL NEEDS DAN AUDITOR SWITCHING DALAM PERSEKTIF FRAUD TRIANGLE TERHADAP FINANCIAL STATEMENT FRAUD (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2012-2017) - Luthfia Putri Salsabila; Raja Adri Satriawan Surya; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
The purpose of this research is to know the effect of financial stability, ineffectivemonitoring, personal financial needs, and auditor switching to financial statement fraud.According to Donald Cressey (1953) to tell that there are three general perspectives inconducting the triangle fraud. The three perspectives are pressure, opportunity, andrationalization. Therefore, each category has its own conditions which can be used asvariables in this study. The population of this research is manufacturing companies listedon the Indonesia Stock Exchange in 2012-2017. The sample selection was done usingpurposive sampling technique and obtained a sample of 68 companies. In this studyassisted with SPSS version 17. Testing the hypothesis in this study using multipleregression analysis. The results of this research indicate that ineffective monitoring isproxied by the number of board of commissioner meetings, personal financial needsproxied by insider ownership ratios, and auditor switching measured by dummyvariables to show that there are not significantly influence financial statement fraud.While financial stability is proxied by a percentage change in total assets to shows thatthere is a significant influence toward financial statement fraud.Kata kunci : Financial Statement Fraud, Financial Stability, Ineffective Monitoring,Personal Financial Needs, Auditor Switching.